DESIGNING OF NOVEL TOPICAL IN SITU POLYMERIC FILM-FORMING SOLUTION SPRAY FORMULATION OF ANTIFUNGAL AGENT: IN VITRO ACTIVITY AND IN VIVO CHARACTERIZATION - ABDULLAH, NABIL; PATIL, AMIT B. (International Journal of Applied Pharmaceutics, 2022)
Objective: Voriconazole (VCZ) is a broad-spectrum antifungal medication that works by inhibiting fungal Cytochrome P450, preventing fungi growth. The current study aims at developing and characterizing an antifungal in situ film-forming polymeric solution spray containing VCZ for use in topical drug delivery systems. Methods: Optimized VCZ in situ polymeric film formulation was evaluated for Fourier transform infrared spectroscopy (FTIR), differential scanning calorimeter (DSC), X-ray diffractometry (XRD), Scanning electron microscope (SEM), in vitro and in vivo, ex-vivo investigation using abdominal rat skin and stability studies. The in vivo antifungal activity of the advanced in situ film was examined in albino Wistar rats. Results: The optimized batch contained 22% Eudragit RS 100 (ERS) and 4% Sorbitol. Based on FTIR, XRD, SEM, and rheological studies. Formulation ingredients of VCZ loaded topical in situ polymeric film spray were observed to be compatible and showed no evidence of precipitation, deformation, or discoloration. Diffusion test (in vitro %), and ex-vivo drug diffusion % obtained 99.22%, and 97.45% respectively. The maximum inhibition zone was measured at 13±0.07 mm. The Wistar rat was employed as an animal model for skin irritation and antifungal studies. A study of short-term stability observed no significant modifications in the physical properties. Conclusion: The findings of the optimized VCZ topical in situ polymeric film spray formulation were satisfactory, demonstrating comparable improvement in superficial antifungal treatment.